The Metabotropic Glutamate Receptor Mgl-2 Modulates Satiety And Serotonergic Signaling In Caenorhabditis Elegans - Lacour, Ailin (2024)
The ability to perceive nutritional status is crucial for modulating animal behavior. In this study, we explore the mechanisms by which C. elegans senses its nutritional state. We discovered that mutants in mgl-2, the C. elegans ortholog of mammalian metabotropic glutamate receptors (mGluRs), exhibit hyperphagia and a pronounced reduction in locomotion when exposed to food. While these behaviors are typical of starved animals, these mutants display them even without prior food deprivation. This hyperphagic behavior leads to increased lipid accumulation, indicating that MGL-2 is essential for the perception of satiety in these animals. In starved wild-type animals, encountering food triggers an exacerbated release of serotonin, which allows the animal to increase its feeding rate and slow down locomotion to restore its nutritional status. Through genetic experiments and in vivo neuronal activity measurements, we determined that MGL-2-mediated nutritional state perception is necessary to temper serotonergic signaling in fed animals. We are currently working to identify the specific neurons where MGL-2 exerts these effects. We propose that MGL-2 serves as a key modulator within neural circuits that control appetite and energy homeostasis. Notably, mammalian mGluRs have recently been implicated in hunger and satiety perception. Given the conservation of fundamental processes across the animal kingdom, our study provides potentially universal insights into feeding behaviors.